THE CONTRIBUTION OF THE CULTURE OF ENTREPRENEURSHIP TO ENHANCING THE SELF-AWARENESS OF HUMAN RESOURCES (Hema Plastic Company as a Model) - Burhan Hamad Idham; Mohamed Hussein Gharbi (Scholars Digest Publishing, 2024)
Given the significant shifts and intensifying competition and global exposure that companies are currently experiencing, as well as the ongoing growth and intensifying competition amongst them, they are searching for ways to establish an entrepreneurship culture that is hard to replicate and attain superiority over their rivals. One such strategy is to empower employees and raise their level of self-awareness. Accordingly, the research goal is to determine the degree to which the entrepreneurship culture enhances the self-awareness of human resources.A questionnaire was created to gather research data, and the research model and its assumptions were developed based on the research literature, prior studies, and research measurements, and a questionnaire was created in order to gather research data. A total of 69 questionnaires were distributed, of which 67 were recovered with a 97% response rate. The Crouch Nabach alpha test was utilized to confirm the degree of reliability in the data, and the path method and structural equation modeling were employed to test hypotheses. The study produced a number of findings, the most significant of which was that the variables—originality and creativity—had an effect on abilities. Regarding the elements that improve human resource self-awareness (innovation), they refute the theory. It is evident from this that innovation has little effect on abilities.
Keywords: Self-awareness, entrepreneurship, and Hema Plastic Company as a model